Model Persamaan Struktural Pola Usahatani Padi-Jeruk Lahan Gambut Tropikal Berkelanjutan di Kabupaten Barito Kuala Kalimantan Selatan - Muhammad Husaini; Masyhuri Masyhuri; Dwijono Hadi Darwanto; Jangkung Handoyo Mulyo (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
The study aims are: (1) to analysis establishment indicators of exogenous and endogenous latent; (2) to formulate structural equation model for many sustainable farming system and analyze those forming variables; (3) to analyze the impact of farmer capacity, production factors availability, capital farmer condition, economics and physical condition, to farmer management capacity, and (4) to analyze the impact of farmer management capacity to sustainable farming system. Forming indicators are 30 variables, both latent exogenous and endogenous, and 27 of those variables can be confirmed and give significan contribution to exogenous latent variables and endogenous latent variables. Model-I, has been restricted as the best for the structural equation modelling. Parameter estimation showed that the farming capacity management to manage farming system paddy-citrus is dominant and it is significantly determined by the capital farmer condition, which is composed and contributed dominantly by source and acces to capital. The sustainability of this farming system is significantly determined by farmer management capacities which is composed and contributed dominantly by the farmer activities planning.